PERANCANGAN SISTEM APLIKASI GUDANG TOKO ANGKASA JAYA MOTOR BERBASIS WEB MENGGUNAKAN NODE.JS - Balino, Ical Ferin; Beeh, Yos Richard (STKIP PGRI Tulungagung, 2024)
In carrying out its business activities, Angkasa Jaya Motor stores often experience problems in managing and storing goods in the warehouse. The problem occurs because the store still employs manual work methods in its business processes. One of them is that the process of recording goods still utilizes a notebook. The data recorded in the notebook is then transferred to the spreadsheet tool. In this process, data synchronization is also a constraint. There are data discrepancies between the stock data in the inventory, notebooks, and spreadsheet tools, thereby affecting the accuracy of the goods data. The research aims to develop a Web-based warehouse application using Node.js to help address these issues. The method used in this research is the Research and Development (RD) method. This research yields a Web-based warehouse application system that enables employees to conduct inventory management more practically and optimize warehouse operations and data integration helps store owners efficiently access real-time information goods on the inventory, so that enable business decisions to be made based on accurate data.